Preserving the Naturalness of the Kazakh Language as a National Language: An Ecolinguistic Analysis - Auganbayeva, Markhaba; Mauytova, Zhannur; Alkaya, Ercan; Beisenuly, Zhakyp; Mamayeva, Gulnar; Abdualiuly, Bekzhan (Florida Gulf Coast University, 2026)
This study examines efforts to preserve the naturalness and sustainability of the Kazakh language from an ecolinguistic perspective. A systematic review method is employed, analyzing 32 academic publications obtained from designated databases covering the period 2020–2025. The findings indicate that language preservation relies on structural interventions such as national language policies, public prestige, and alphabet reform. Lexical strategies that balance terminology modernization with the preservation of traditional cultural discourse and educational policies that prioritize national identity and standardized norms were also within those structural interventions. The findings reveal that globalization (English) and historical language hierarchies (Russian) have narrowed the language's academic and public functions, and digitalization has presented opportunities and led to normative deviations. Ultimately, the ecological sustainability of the Kazakh language requires a holistic, proactive, and data-driven governance model that integrates policy, education, and digital technology, beyond merely prescriptive or simplistic approaches. This study offers a theoretical synthesis and a practical roadmap for language planners by outlining policy-oriented strategies, education-based interventions, and technology-supported mechanisms for sustaining linguistic naturalness. © 2026 by Author/s and Licensed by CECS Publications, United States.
Keywords: Ecolinguistics; Kazakh Language; Language Naturalness; Language Preservation; Turkic Languages